Is seniority of emergency physician associated with the weekend mortality effect? An exploratory analysis of electronic health records in the UK. Issue 12 (30th October 2019) - Han, Larry; Fine, Jason; Robinson, Susan M; Boyle, Adrian A; Freeman, Michael; Scholtes, Stefan
Abstract : Objective: Admission to hospital over a weekend is associated with increased mortality, but the underlying causes of the weekend effect are poorly understood. We explore to what extent differences in emergency department (ED) admission and discharge processes, severity of illness and the seniority of the treating physician explain the weekend effect. Methods: We analysed linked ED attendances to hospital admissions to Cambridge University Hospital over a 7-year period from 1 January 2007 to 31 December 2013, with 30-day in-hospital death as the primary outcome and discharge as a competing risk. The primary exposure was day of the week of arrival. Subdistribution hazards models controlled for multiple confounders, including physician seniority, calendar year, mode of arrival, triage category, referral from general practice, sex, arrival time, prior attendances and admissions, diagnosis group and age. Results: 229 401 patients made 424 845 ED attendances, of which 158 396 (37.3%) were admitted to the hospital. The case-mix of admitted patients was more ill at weekends: 2530 (6.4%) admitted at a weekend required immediate resuscitation compared with 6450 (5.4%) admitted on a weekday (p<0.0001). Senior doctors admitted 24.8% of patients on weekdays and 24.0% at weekends, but junior doctors admitted 61.7% of patients on weekdays and 44.2% at weekends. 3947 (3.3%) patients admitted on a weekday and 1454 (3.7%) patients admitted at a weekend died within 30 days. In the adjusted subdistribution hazards model, the HR of in-hospital death was 1.11 (95% CI 1.04 to 1.18) for weekend arrivals. After controlling for confounders, the in-hospital mortality of patients admitted by junior doctors was greater at the weekend (adjusted HR (aHR) 1.15, 95% CI 1.06 to 1.24). In-hospital mortality for patients admitted by senior doctors was not statistically different at the weekend (aHR 1.08, 95% CI 0.98 to 1.19). Conclusions: Our findings suggest that the weekend effect was driven by a higher proportion of admitted patients requiring immediate resuscitation at the weekend. Junior doctors admitted a lower proportion of relatively healthy patients at the weekend compared with the weekday, thus diluting the risk pool of weekday admissions and contributing to the weekend effect. Senior doctors' admitting behaviour did not change at the weekend, and the corresponding weekend effect was reduced.